"Me Getting Plastered and Her Provoking My Eyes": Young People's Attribution of Blame for Sexual Aggression in Public Drinking Spaces. (July 2015) - Becker, Sarah; Tinkler, Justine
Barroom sexual aggression—especially unwanted groping, kissing, and touching—is ubiquitous and largely unregulated. While research explicates how alcohol interacts with other precipitating factors to cause incidents like fistfights, the causes of less serious forms of sexual aggression remain understudied. Normalization of non-consensual sexual contact in bars means much of it goes unnoticed and is difficult to quantify or predict using conventional statistical methods. We use 126 young people's narratives about experiences with barroom aggression to explore how/when it is tolerated or socially sanctioned. We find that alcohol, context, and gender shape attributions for sexual aggression in public drinking settings.